A Conceptual Framework for Value Creation through Sustainability Reporting and Intellectual Capital - Siti Almurni; I Gusti Ketut Agung Ulupui; Susi Indriani (Research of Finance and Banking, 2026)
The growing importance of sustainability and knowledge-based resources has increased interest in understanding how organizations create value in dynamic business environments. Previous studies have reported positive relationships between sustainability reporting, intellectual capital, and firm value, but these constructs have largely been examined independently, providing limited explanation of how sustainability-related and knowledge-based resources interact through innovation. This study addresses this gap by proposing a conceptual framework that positions innovation performance as the strategic mechanism linking sustainability reporting and intellectual capital to organizational value creation. Using a theoretical research approach, the study integrates Stakeholder Theory, Legitimacy Theory, the Resource-Based View, and Dynamic Capabilities Theory through a structured literature review. The study’s conceptual novelty lies in presenting a theoretically integrated value-creation framework explaining how sustainability reporting and intellectual capital jointly enhance sustainable organizational value through innovation performance. By moving beyond the direct relationship perspective adopted in prior research, the proposed framework offers a mechanism-based explanation of how sustainability-related and knowledge-based resources are transformed into innovation capabilities that ultimately generate sustainable organizational value, providing directions for future empirical research and managerial practice.